Translation and cross-cultural adaptation of the young children participation and environment measure for its use in Austria, Germany, and Switzerland - Krieger, Beate; Ederer, Friedrich; Amann, Ruth; Morgenthaler, Thomas; Schulze, Christina; Dawal, Britta (Frontiers in Pediatrics, 2024)
Background: Concepts such as participation and environment may differ across cultures.Consequently, cultural equivalence must be assured when using a measure like the Young Children Participation and Environment Measure (YC-PEM) in other than the original English-speaking contexts. This study aimed to cross-culturally translate and adapt the YC-PEM into German as it is used in Germany, Austria, and Switzerland.Methods: Following international guidelines, two translations were compared, and the research and an expert team made the first adaptations. Twelve caregivers of children with and without disabilities from three German-speaking countries participated in two rounds of think-aloud interviews. Data were analyzed by content analysis to look for item, semantic, operational, conceptual, and measurement equivalence to reach a cultural equivalence version in German commonly.Results: Adaptations were needed in all fields, but prominently were item, operational, and conceptual equivalence. Operational equivalence resulted in graphical adaptations in the instructions and questions to make the German version of YC-PEM, YC-PEM (G), more userfriendly.German version of the YC-PEM suitable for Germany, Austria, and Switzerland. A culturally adapted YC-PEM (G) is now available for research, practice, and further validation.Next, the YC-PEM (G) must be applied and tested to establish psychometric properties, reliability, and validity for different groups of young children and practice contexts. It also needs to be disseminated in German-speaking contexts.This study presents a cross-cultural translation and adaptation process to develop a German version of the YC-PEM that is suitable for three German-speaking countries. As participation and environment are both complex concepts to measure, item equivalence and conceptual equivalence posed the greatest challenges for this cultural adaptation. The adaptation captivates through new graphical instructions to ease understanding and processes to fill in the assessment correctly. With extensive input from parents, experts, researchers, and the YC-PEM team from CanChild, a culturally adapted version of YC-PEM (German) is now available for research, practice, and further validation.